Total free lipids from MDR strain of Mycobacterium tuberculosis “M” reduce T cell activation and CTL activity in healthy individuals - Bigi, María Mercedes; Imperiale, Belen Rocio; Soria, Marcelo Abel; López, Beatriz; Bigi, Fabiana; Barrera, Silvia Susana de la (Elsevier, 2025)
Increasing evidence highlights the role of cell wall components in the effectiveness of different Mycobacterium tuberculosis (Mtb) strains in modulating host immune response. We previously demonstrated that the outbreak multidrug-resistant strain M displays a distinctive lipid profile in its cell envelope compared to the closely related sporadic strain 410. Both strains markedly differ in their ability to induce fully functional CD8+ T cells because of low CD69 signaling and impaired CD4+ T cell help. In this study, we evaluated the impact of extractable lipids (LP) from M (LP-M) and 410 (LP-410) on the activation and functionality of T cells from healthy individuals. PBMCs were cultured alone or with Mtb in the presence or absence of LP-M, LP-410, or LP from CD1551 mutants in polymorphic genes between M and 410. Then, surface CD69 and intracytoplasmic IL-2 (after 3 days of culture), as well as surface CD107 expression (after 6 days of culture) were determined in T cells by flow cytometry. In contrast to LP-410, LP-M induced low expression of CD69 and IL-2 in CD4+/CD8+ cells and of CD107 in CD8+ cells. Besides, LP from Mtb strains mutated in Rv1861c and Rv3787c genes inhibited H37Rv-induced T cell response without causing cell death. Thus, our results suggest that LP-M likely through mutations in Rv1861 and Rv3787c, inhibits the activation and functionality of T cells from PPD+ healthy human donors and might partially contribute to the development of immune evasion mechanisms in the M strain.